Farm laws debate: A bit of analytical rigour and global best practices - Roy, Devesh; Pradhan, Mamata; Boss, Ruchira (The Rise, 2020)
There are several lessons to learn from the experiments in the past, like the repeal of APMC in Bihar and the institution of e-NAM, which have elements of the current farm acts. History of little success will be repeated if the mechanics of trading are not understood and actions are not taken to alleviate the constraints.